2020
DOI: 10.3390/ijerph17228361
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Mechanism of Job Satisfaction on Safety Behavior of New Generation of Construction Workers Based on Chinese Context: The Mediating Roles of Work Engagement and Safety Knowledge Sharing

Abstract: China’s construction industry developed rapidly and safety production has become a vital issue. Improving the safety behavior of construction workers is an important measure to effectively decrease construction safety accidents. At present, a New Generation of Construction Workers (NGCWs) born after 1980 has gradually become the main force of construction companies in China and the special group characteristics coming from the intergenerational difference may make them behave differently in safety-related acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 122 publications
1
27
0
2
Order By: Relevance
“…Job satisfaction is an indicator in producing maximum work behavior (Ni et al, 2020;Tafzal Haque et al, 2019). It comes from what an organization has given its members.…”
Section: The Effect Of Job Satisfaction On Organizational Citizenship Behaviormentioning
confidence: 99%
“…Job satisfaction is an indicator in producing maximum work behavior (Ni et al, 2020;Tafzal Haque et al, 2019). It comes from what an organization has given its members.…”
Section: The Effect Of Job Satisfaction On Organizational Citizenship Behaviormentioning
confidence: 99%
“…The results of this study are in line with an earlier study, which stated that in the welding process at the Wijaya welding workshop, the severity value of short-circuit electric shock was 9. Trips or collision with electric equipment also might lead to electric shock [16]. Several other studies have also stated that electric shock in the welding process is the highest risk of danger that often occurs in the welding process [13,[17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Another study on the occupational exposure to stainless steel welding fumes conducted by Vol. 16 Stanislawska, stated that manganese, chromium, and nickel were found in the blood of welders as a result of exposure to fume particles [24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Using these criteria, the following types of studies were not included: studies that formed an overall measure of employee engagement that combined Saks' (2006) job engagement and organization engagement scales to form an overall measure of employee engagement (Biswas and Bhatnagar, 2013;; studies that combined Saks' (2006) measure of organization engagement with work engagement scale items to measure work or employee engagement (Morokane et al, 2016;Ni et al, 2020); studies that measured organization engagement and job engagement but reported the results for both measures together rather than independently (Piyachat et al, 2014) and studies that used Saks' (2006) measure of organization engagement but changed the target of engagement (e.g. community, Haas et al, 2021).…”
Section: Sample and Inclusion Criteriamentioning
confidence: 99%